A combined precipitation-adsorption method for harmless treatment of glyphosate mother liquor. (10th February 2023) - Li, Zhanhui; Wang, Yi; Zhou, Ruyi; Yu, Junxia; Li, Xiaodi; Xiao, Chunqiao; Hou, Haobo; Chi, Ruan; Feng, Guoqing
Abstract: A large amount of glyphosate mother liquor containing high concentrations of several phosphorous-based compounds, namely glyphosate, phosphorous acid, and glyphosine at a concentration of 34 g/L, is generated in the production of the most widely used organophosphorus herbicide and poses a grave threat to the environment. In this study, a combined method of precipitation and resin adsorption was used for the harmless treatment of the mother liquor. Firstly, most of the phosphorous-based compounds in the mother liquid were precipitated by metal ions of Ca 2+, and then the excess metal ions and the remained phosphorous compounds in the supernatant were removed by using 001*7 and D301 resin, respectively. Results showed that 98.9% of the phosphorous compounds could be precipitated by Ca 2+, and the residual concentration of Ca 2+ and total phosphorus were 1.2 and 0.4 g/L, respectively, after this treatment. Adsorption experiment results showed that the 001*7 resin had the high adsorption capacity of 52.9 mg/g for Ca 2+, and it almost did not absorb glyphosate, phosphorous acid, and glyphosine (adsorption capacity of them all <0.1 mg/g) in the investigated pH range from 1.0 to 8.0. The D301 resin performed well under dynamic adsorption conditions, with adsorption capacities of 233.3, 90.3, and 89.6 mg/g for glyphosine, phosphorous acid, and glyphosate, respectively, at a flow rate of 7.2 mL/min. When using tandem columns fixed with 001*7 and D301 resins to treat the supernatant from the precipitation step, the concentrations of Ca 2+ and total phosphorus decreased significantly to 1.5 and 0.5 mg/L, respectively, and reached the discharge standards for industrial wastewater. The technology proposed in this study has great application potential in the glyphosate production industry. Graphical abstract: Image 1 Highlights: Ca 2+ could remove 98.9% of Tp from glyphosate mother liquor at low temperature and high pH. The adsorption performances of 001*7 resin toward Ca 2+ were investigated. The removal efficiencies of D301 resin toward phosphorus compounds under dynamic condition were explored. The proposed method of precipitation and resin adsorption could achieve the harmless treatment of glyphosate mother liquor.